Dependency of flow-mediated vasodilatation from basal nitric oxide activity - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Jung, Susanne; Striepe, Kristina; Ott, Christian; Delles, Christian; Schmieder, Roland (Clinical Physiology and Functional Imaging, 2021)
Background: Flow-mediated vasodilatation (FMD) has become one of the most widely assessed parameters to analyse endothelial and vascular function in cardiovascular medicine. The degree of contribution of nitric oxide (NO) to FMD is inconclusive and varies widely depending on the device used. In this study, we used a semi-automatic ultrasound device to analyse to what extent basal NO activity contributes to FMD of the brachial artery. Methods: FMD was assessed with the UNEX EF device in a cross-over single blinded randomized study at baseline and then during infusion of either a NO-synthase-inhibitor (NG-monomethyl-L-arginine (L-NMMA)) or saline. The analysis was repeated after 1 week with the alternative infusion of L-NMMA or saline. All measurements were analysed both automatically and by a technician manually. Results: In total, 25 healthy men subjects completed the study. Diastolic blood pressure and heart rate significantly changed during infusion of L-NMMA. Infusion of L-NMMA reduced FMD significantly (−37%, p = 0.002). Saline solution had no effect on FMD (+14%, p = 0.392). Change in FMD was significantly different between the groups (ΔFMDL-NMMA vs. ΔFMDsaline, p = 0.032). There was a statistically significant correlation between automatically analysed results and those obtained by an experienced technician (FMDsaline: r = 0.822, p < 0.001; FMDL-NMMA: r = 0.645, p = 0.007). Conclusion: The influence of NO on FMD is approximately 40% if assessed using the UNEX EF. Prior to use FMD as a marker of endothelial dysfunction, we should explore different methods including various duration of forearm ischaemia to increase NO dependency of FMD.
CRIS-Team Scopus Importer:2021-04-02
Keywords: basal nitric oxide activity; flow-mediated vasodilatation; UNEX EF